Effects of supplementing growing-finishing pig diets with Bacillus spp. probiotic on growth performance and meat-carcass grade qualitytraits - Balamuralikrishnan Balasubramanian (Revista Brasileira de Zootecnia, 2016)
ABSTRACT Seventy five pigs [(Landrace × Yorkshire) × Duroc] with an initial body weight of 23.3±1.40 kg were used in the present study to investigate the influence of supplementation of a Bacillus spp. combination as probiotic (0%, 0.01%, and 0.02% with basal diet) in growing-finishing pig diets on performance parameters with a feeding trial period of 16 weeks. Growth performance was analyzed at the start and at weeks 6, 12, and 16 of the experimental period. The entire experiment using probiotic supplementation in the diet revealed significant differences in average daily gain and gain:feed, but no effects on average daily feed intake. The result showed significant effects on digestibility of dry matter (0.002), nitrogen (0.069), and energy (0.099) at week 16; and number of fecal Lactobacillus (0.082, 0.041), E. coli (0.097, 0.052), and blood glucose (0.001, 0.049) at weeks 6 and 16. Dietary supplementation with Bacillus spp. probiotic resulted in a significant linear effect on sensory evaluation of meat color, drip loss at day 3, and carcass weight in pigs. In contrast, there was no significant difference in blood metabolic profiles and noxious gas emissions in this experiment. Dietary combination of Bacillus spp. can be used as a probiotic for enhancing the growth performances and carcass quality of growing-finishing pigs.